2017
DOI: 10.3390/nu9080874
|View full text |Cite
|
Sign up to set email alerts
|

What Is Nutritious Snack Food? A Comparison of Expert and Layperson Assessments

Abstract: The term “nutritious” is being increasingly used by product manufacturers but the term is not currently regulated as a nutrition claim. It is unclear how lay consumers and experts define and interpret the term or how they evaluate the “nutritiousness” of various foods. To address this evidence gap, a mixed methods design was applied and both nutrition experts (n = 206) and lay participants (n = 269) provided definitions of the term “nutritious” and evaluated the “nutritiousness” of 20 different snack foods in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Leximancer is a text mining software application that was developed by researchers at the University of Queensland, Australia, to code automatically large qualitative datasets, and has since been validated and applied in various research dimensions . The software has been used in primary research to explore and develop definitions for terms such as “nutrients” and “disaster resilience” and to analyze opinion polls and transcripts from online discussion groups . It has been used to compare the conceptual similarity of perceptions between stakeholder groups and extended to explore interactional dynamics of real‐life conversations .…”
Section: Introductionmentioning
confidence: 99%
“…Leximancer is a text mining software application that was developed by researchers at the University of Queensland, Australia, to code automatically large qualitative datasets, and has since been validated and applied in various research dimensions . The software has been used in primary research to explore and develop definitions for terms such as “nutrients” and “disaster resilience” and to analyze opinion polls and transcripts from online discussion groups . It has been used to compare the conceptual similarity of perceptions between stakeholder groups and extended to explore interactional dynamics of real‐life conversations .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we found that the impact of social identity remained when accounting for the perceived healthfulness of foods. Lay perceptions of healthfulness may differ from expert opinions (Bucher, Hartmann, Rollo, & Collins, 2017), limiting the extent to which our data may speak to actual healthy eating, but these data suggest that identity influences evaluation above and beyond people's own perceptions of healthfulness.…”
mentioning
confidence: 61%
“…However, as outlined previously, the meaning of the term currently remains unclear and different definitions are used; therefore, ascertaining consumer and health professional awareness and understanding of nutrient density is difficult. In this context, it is interesting that a recent study reported very different terminology used to define the ‘nutritiousness’ of foods by experts (who used terms such as nutrient density, macronutrients, micronutrients, kilojoules and calories) compared to consumers (who used terms such as fuel, fresh, natural, body needs and functioning) (Bucher et al ). More recently, a survey of 1000 adults in the US revealed that nearly two‐thirds of respondents had at least heard of nutrient density; however, only 24% felt confident that they knew what the term meant and that they would be able to explain it to someone else (International Food Information Council Foundation ).…”
Section: Communication and Behaviour Changementioning
confidence: 99%
“…This requires starting with the consumer; thinking about their perspective, experience and needs; and finding solutions that they can understand, make meaning of and appreciate. Research suggests that terminology such as ‘nutrient density’ is used only by limited audiences, and so, there is a need for translation into language understood and preferred by consumers in order to engage them in discussions about diet quality (Bucher et al ). Effective communication of nutrient density may perhaps best be undertaken with the support of behaviour change and communications experts, with a focus on the actionability and memorability of messages, activating people’s behaviour using recognised techniques (such as ease of visualisation, chunking and sequencing information into manageable units, specifying when to act and embedding triggers) (Ratner & Riis ).…”
Section: Communication and Behaviour Changementioning
confidence: 99%